Circular RNAs in stem cells: from basic research to clinical implications. Issue 1 (28th January 2022) - Lu, Hui-Juan; Li, Juan; Yang, Guodong; Yi, Cun-Jian; Zhang, Daping; Yu, Fenggang; Ma, Zhaowu
Abstract: Circular RNAs (circRNAs) are a special class of endogenous RNAs with a wide variety of pathophysiological functions via diverse mechanisms, including transcription, microRNA (miRNA) sponge, protein sponge/decoy, and translation. Stem cells are pluripotent cells with unique properties of self-renewal and differentiation. Dysregulated circRNAs identified in various stem cell types can affect stem cell self-renewal and differentiation potential by manipulating stemness. However, the emerging roles of circRNAs in stem cells remain largely unknown. This review summarizes the major functions and mechanisms of action of circRNAs in stem cell biology and disease progression. We also highlight circRNA-mediated common pathways in diverse stem cell types and discuss their diagnostic significance with respect to stem cell-based therapy.